Bantuan dan Kemitraan Terhadap Tingkat Pendapatan UMK Pengolahan Hasil Perikanan di Indonesia - Agus Triyanto; Muhammad Syamsun; Amiruddin Saleh (Institut Pertanian Bogor, 2012)
Micro and Small Enterprises has a strategic role in national economy, especially in employment absorption, increase incomes and generate economic activity. Since the economic crisis hit Indonesia in 1998, the role of MSEs increased sharply, as it turns out large-scale efforts many are fragile and fall caused by the economic crisis. The general objective of this study is to examine the outcome of the policy and provide input for decision-makers about the MSEs. Specifically this study aims to (1) Identify the types of assistance/aid and partnership provided by the government, private and cooperative services to MSEs, (2) Perform analysis of income levels MSE, (3) Perform analysis of the effect of assistance and partnership on income of MSEs. The analysis performed are descriptive analysis by cross tabulation and statistical inference by using the mean difference test, using analysis of variance (ANOVA), after performing the test assumptions. In general, from the 1.785 sample there are 48,29% of MSEs male entrepreneurs, and aged between 30-59 years (82,02%), with the majority of education is below elementary school (74,73%). MSEs receiving assistance/aid and partnership, its production capacity distributed at the level of 51-75 percent and 75% upwards. There is a 72,92% of MSEs that received assistance and partnerships who have difficulty. The results of inferential analysis indicate that there are significant differences at average benefit without treatment with MSE receiving assistance/aid and the MSE with partnership, but there is no significant difference between MSE without treatment with MSE with both receiving assistance/aid and partnerships